2014
DOI: 10.1177/0003319714547946
|View full text |Cite
|
Sign up to set email alerts
|

Association of 5 Well-Defined Polymorphisms in the Gene Encoding Transforming Growth Factor-β1 With Coronary Artery Disease Among Chinese Patients With Hypertension

Abstract: We assessed the association between 5 well-defined polymorphisms of the transforming growth factor-β1 (TGFB1) gene and coronary artery disease (CAD) among patients with hypertension from northeast China. All study participants were classified into patients with CAD (n = 679) and controls (n = 686) according to angiographic results. Genotyping was carried out with the ligase detection reaction method. In single-locus analysis, only genotypes of rs1800469 differed significantly between patients with CAD and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…TGF- β 1 is also a differentiation and growth regulator with multiple functions and plays a vital role in inflammatory response and tissue repair [ 17 ]. 5-HT is a monoamine released by platelets and mast cells after tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…TGF- β 1 is also a differentiation and growth regulator with multiple functions and plays a vital role in inflammatory response and tissue repair [ 17 ]. 5-HT is a monoamine released by platelets and mast cells after tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of polymorphisms in genes encoding different enzymes, receptors, and growth factors on ISR or CAD are being actively investigated. Previously published reports have suggested a relationship between the occurrence of ISR or CAD and genetic variation occurring as single nucleotide polymorphisms (SNPs) in the endothelial nitric oxide synthase gene ( eNOS ) [ 11 13 ], the angiotensin converting enzyme gene ( ACE ) [ 14 ], the angiotensin II type 1 receptor gene ( AT1R ) [ 15 , 16 ], TGF-β [ 17 19 ], and VEGF [ 20 , 21 ]. However, the potential roles of functional polymorphisms in these genes in restenosis of DES have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding rs1800468 (−800G/A), CTS patients had an increased frequency of major allele G. It is controversial that minor allele A > G is associated with the occurrence of cervical cancer [ 42 ] and coronary heart disease [ 43 ]. In addition, our results showed that the minor protective A allele (GA and AA) resulted in a significant increase in serum TGF-β1 and MIP-1β levels compared with those carrying the major risk allele, G. Bogacz et al [ 44 ], reported that renal transplant patients with the A allele rs1800468 required a slightly lower dose of the immunosuppressant tacrolimus-TAC than patients with the G allele.…”
Section: Discussionmentioning
confidence: 99%